An Extension Guideline of Beef Cattle Production in 3 Southern Border Provinces - ลิ้มเจริญ สมนึก; คงเสน มงคล; บุรีรัตน์ อนุชาติ; ไทยบุรี ณฤทธิ์; ตรีมณี สุนีย์ (Princess of Naradhiwas University Journal, 2019)
The objectives of this study were to: 1) study beef cattle production, 2) describe the needs for extension, 3) compare different productions, 4) identify problems of extension, and 5) develop an extension guideline on beef cattle production in the 3 southern border provinces of Thailand. Simple Random Sampling was used to obtain 396 farmers and 30 livestock officers, who all answered to an assessment form. Reliability of questionnaire was confirmed by using Cronbach’s alpha coefficient, yielding a value of 0.96. Data were collected by using interview forms, and then analyzed by using frequency, percentage, minimum and maximum, value mean, standard deviation, and F-test. Results revealed that farmers were: 1) native beef cattle raising (59.6%), 2) not growing grass (37.4%), 3) doing pasture grazing naturally (39.1%), 4) beef cattle breeders (47.5%), 5) using vaccination for foot and mouth disease (55.8%), and puberty cattle (94.7%). The needs for extension were high in beef cattle breeding as well as in managing herd beef cattle at each growing stage and for beef cattle health management. In terms of extension methods, farmer needed highly level in farm visit, promotion of beef cattle group establishment, study trip, and training. The needs for support from related government organizations were at a high level, including: providing bull, vaccination, internal and external parasitic control, and establishing beef cattle auction market at the district level. Regarding the comparisons of needs for extension for beef cattle by variables (age, education, beef cattle breeds, and farmer occupation), results showed that each factor was statistically significant differences (P<0.05). There was a high level in the problems of beef production as following: lack of budget, lack of beef cattle, lack of animal food, lack of forage grass, lack of knowledge of farm management, and lack of livestock officers from government organizations. In extension guideline of beef cattle production in three southern border provinces, it should focus on extension of beef cattle system, production, methods for extension of beef cattle, as well as knowledge of production on beef cattle system.